Group decision making in manufacturing systems: An approach using spatial preference information and indifference zone. (April 2020) - Yu, Chunlong; Matta, Andrea; Semeraro, Quirico
Highlights: A group decision making approach is proposed for difficult decision-making problems encountered in manufacturing systems. Properties of the proposed approach are investigated analytically and with numerical experiments. The proposed approach is applied to a real-world packaging line configuration problem. Abstract: Decision making is an essential activity in manufacturing systems when designing production lines, scheduling, etc. Many decision making problems are characterized by multiple conflicting criteria and a large number of alternatives. For these complex decision making problems, it is rational to involve a group of decision makers (DM) for considering different aspects of the problem. This paper proposes an approach for supporting the decision making group to reduce disagreement in the group and obtain a common solution. The proposed approach allows the DMs to specify a region of acceptance, known as indifference zone, in the objective space as preference inputs. This makes the proposed approach applicable to problems with a large number of alternatives. The use of indifference zone concept captures the uncertain nature of preference articulation. Moreover, the indifference zone is shown beneficial in reducing the difficulty of reaching a group common solution. The properties of the proposed method are investigated analytically and with numerical experiments. Finally, the usefulness of the proposed method is shown by tackling a real-world packaging line configuration problem with a large alternative set.